К проблеме этнолингвистического описания западнопричудских свадебных чинов: клятники – клятник - Вадимовна Штейнгольд, Анжелика (Slavistica Vilnensis, 2010)
On the Western coast of Lake Peipsi in Estonia, the traditional Russian wedding ceremony is already lost. But the ethnographic data collected in Estonian Literary Museum in Tartu shows that it was still alive in the 1930s. Depending on the location and style of the wedding, the group of wedding ceremony participants may have included: 1) a chief male assistant to the bridegroom (klyatnik), 2) male attendants to the bridegroom (klyatniki). However, the ritual features and functions of klyatnik/klyatniki as well as the etymology of these designates are not defined distinctly. This article helps to fill the gaps in our knowledge about traditional culture and language of rural Russian-speaking population in Estonia.